Evaluation of exchange rate forecasts for the kronas nominal effective exchange rate - Henrik Degrér; Jan Hansen; Peter Sellin (Sveriges Riksbank, 2001)
In this paper we evaluate the out of sample forecasting performance of a large number of models belonging to a popular class of exchange rate models. Forecasts of the Swedish nominal effective exchange rate for the period 1980-2000 are performed using both single equation estimation and VAR approaches. The forecast horizons used were from 1 to 12 quarters. None of the models evaluated could convincingly outperform a random walk alternative.
Keywords: F31; F41; F47; 330; Exchange rates; monetary approach; forecasting